Good reasons to leave home: proximate dispersal cues in a social spider. (16th May 2016) - Berger‐Tal, Reut; Berner‐Aharon, Na'ama; Aharon, Shlomi; Tuni, Cristina; Lubin, Yael
Summary: Natal dispersal is a successful tactic under a range of conditions in spite of significant costs. Habitat quality is a frequent proximate cause of dispersal, and studies have shown that dispersal increases both when natal habitat quality is good or poor. In social species kin competition, favouring dispersal may be balanced by the benefits of group living, favouring philopatry. We investigated the effect of changes in the local environment on natal dispersal of adult females in a social spider species, Stegodyphus dumicola (Araneae, Eresidae), with a flexible breeding system, where females can breed either within the colony or individually following dispersal. We manipulated foraging opportunities in colonies by either removing the capture webs or by adding prey and recorded the number of dispersing females around each focal colony, and their survival and reproductive success. We predicted that increasing kin competition should increase dispersal of less‐competitive individuals, while reducing competition could cause either less dispersal (less competition) or more dispersal (a cue indicating better chances to establish a new colony). Dispersal occurred earlier and at a higher rate in both food‐augmented and web‐removal colonies than in control colonies. Fewer dispersing females survived and reproduced in the web‐removal group than in the control or food‐augmented groups. The results support our prediction that worsening conditions in web‐removal colonies favour dispersal, whereby increased kin competition and increased energy expenditure on web renewal cause females to leave the natal colony. By contrast, prey augmentation may serve as a habitat‐quality cue; when the surrounding habitat is expected to be of high quality, females assess the potential benefit of establishing a new colony to be greater than the costs of dispersal. Abstract : By manipulating foraging conditions, the authors increased individual dispersal in a cooperative breeding spiders. They conclude that dispersal is highly sensitive to short‐term changes in local conditions, and sociality in spiders is maintained by both costs of dispersal and benefits of cooperation.